The Effect of Business Environment and Innovation Spirit on Competitive Advantages and Implications on Marketing Performance of Ulos Weaving in North Sumatra - SIHOMBING, Nikous Soter; SIHOMBING, Anton (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018DO - 10.14505//jemt.v9.8(32).18, 2019)
The purpose of this study is to obtain empirical evidence and find clarity of phenomena and conclusions about the influence of business environment and innovation spirit to competitive advantage and its implications on marketing performance. This research uses descriptive and verification method, with data analysis technique of Structural Equation Modeling (SEM) LISREL program, that is collecting, presenting, analyzing, doing model measurement, and hypothesis testing, and making conclusion and suggestion. The population is owner / leader of SMI weaving ulos which is targeted group by Industry and Trade Office of North Sumatera Province, while sample selection is done proportional cluster stratified random sampling and sample determination by Slovin formula.  The results of this study showed that the business environment, innovation spirit, competitive advantage, and overall marketing performance are in good category. Similarly, the verify analysis proves empirically that (1) the business environment and innovation spirit significantly and positively affect the simultaneous competitive advantage, where the innovation spirit has a dominant influence, (2) the business environment has a significant and positive influence on the competitive advantage, (3) innovation spirit significantly and positively influence to competitive advantage, (4) competitive advantage significantly and positively influence to marketing performance.